Le fonctionnement et l’oralisation des sigles de la presse contemporaine française - oglu Ibrahim, Ulfet Zakir (Kalbotyra, 2021)
This article explores initialisms and acronyms taken from newspapers in the French press. In this article, using data from our study of abbreviated words, we attempt to answer the following questions: How can we shorten a word in French? What are the correct forms (means) of pronunciation of initialisms and acronyms? Can an initialism be considered as a separate (common) word? Before investigating the origin and function of various abbreviations in the French press, the preferred modality of each era, or even the basic rationales behind using such abbreviations, we define a term for abbreviated forms. It seems important to us to present our own definition and to illustrate in detail the problems of the subject. French uses four forms of abbreviated words to help create new words and build vocabulary. These four main forms of abbreviated words are: initials, acronyms, abbreviations, and truncations. At the same time, our goal in this article is to clarify the problem of pronunciation of initialisms and acronyms. To achieve our goal, we used a survey methodology conducted among people from different social groups and ages, in order to determine forms of oral speech and decipher abbreviations of the French daily press. Based on our research, we created a data table on the pronunciation of initialisms in French. The corpus elements and the survey conducted provide us with reliable data on the functioning, interpretation and decoding of abbreviated words in modern French. The survey results allow us to observe the fact that there are two main ways of using abbreviations in French: reading and spelling. Our analysis shows that the obligation to use reading to write an acronym depends, in part, on a number of formal conditions. One of these conditions is the syllable and phonetic structure of acronyms. In conclusion, based on the survey results, we describe the table and types of abbreviations in the corpus of our study.